Allium tsinlingense (Amaryllidaceae, Allioideae), a new species from Shaanxi, China - Xun, Lu-Lu; Liu, Pei-Liang; Lu, Yuan; Zhang, Ya-Wei; Li, Si-Feng; Yue, Ming; Li, Bin; Zhou, Ya-Fu (Phytotaxa, 2022)
A new species, Allium tsinlingense, from southern Shaanxi Province, China, is described and illustrated here. This species is similar to A. maowenense in Allium sect. Daghestanica, but it can be distinguished by its leaves solid, its spathe persistent after flowering, its flowers changing color from green, greenish to white in different stage, but never purplish, with the midvein of tepal greenish and never pale red, and its pedicels with bracteoles at base. Molecular phylogenetic analyses also suggested that this new species is a member of Allium sect. Daghestanica and a sister taxon to A. maowenense.